Analyzing the intellectual structure of research on simulation-based learning in management education, 1960–2019: A bibliometric review. Issue 3 (November 2020) - Hallinger, Philip; Wang, Ray
Abstract: Purpose: This review used science mapping to document and analyze the use of simulation-based learning in management education. Design: The authors used bibliometric tools to analyze 1200 relevant Scopus-indexed documents published between 1960 and 2019. Descriptive statistics, co-citation analysis and co-word analysis were employed in this quantitative review. Findings: The review found a rapidly growing publication trajectory with 81% of documents published since 2000 and 57% since 2010. While this literature is worldwide in scope, publications authored in Anglo-American-European societies accounted for 85% of this corpus. Topical analysis verified that simulation-based learning is being used to teach a wide range of functional management subjects. Co-citation analysis identified four 'schools of thought' that define the intellectual structure of this literature: Theoretical Foundations of Simulation-Based Learning, Simulation-Based Learning in Business Education, Organizational Theory and Complex Systems, Simulation-Based Learning in the Professions. Implications: The review highlights the need for programmatic research which examines the design and instructional use of management simulations across different cultural contexts. In a global management education context, greater attention needs to be given the 'portability' of the underlying theories and decision rules that underlie simulations. More attention should also be given to the use of simulations in management fields outside of business education. Originality/value: The review empirically affirms the impact that theories of human learning have had on the design and use of simulation-based learning and highlights the importance of framing the lessons drawn from simulations when used across different cultural contexts. Highlights: Reviewed 1200 Scopus documents on use of simulations in management education. Used bibliometric analysis to identify trends in the development of this literature. Found a rapidly growing literature largely published in Western, developed societies. Revealed the intellectual structure of the literature comprised of four schools of thought. Concluded that the conceptual anchor of this field lies in education and psychology.